Exosomes: the next frontier in vaccine development and delivery - Tan, Dan; Li, Guangyao; Fu, Wenyan; Lei, Changhai (Frontiers in Immunology, 2024)
Exosomes are small subtypes of extracellular vesicles (EVs) naturally released by different types of cells into their environment. Exosomes refer to small vesicles (30-150nm) containing complex RNA and proteins. Nowadays, they especially refer to disk-like vesicles with a diameter of 40-100nm, which are widely found in body fluids such as blood, saliva, urine and milk, and have the function of cell messenger and participate in cell communication. Almost all types of cells can transmit information and exchange substances between cells through the production and release of exosomes, so as to achieve cell proliferation, differentiation, immune regulation, inflammation regulation, apoptosis and other biological functions. Because it exists widely in various body fluids, it is easy to obtain and detect, and has the application potential of disease diagnosis and prognosis detection. Because exosomes are genetically engineered with targeted proteins, they have better biocompatibility and low immunogenicity. Therefore, exosomes are the preferred vector tools for vaccines. In this review, we describe the characteristics of exosomes and discuss their special and ambiguous functions in the infectious environment. In this regard, we explored the ability of exosomes to carry immunogenic virus antigens and their function in establishing adaptive immune responses. Since exosomes provide an interesting platform for antigen presentation, and vaccines are a powerful means of preventing disease and emerging infectious diseases, we further review the advantages and disadvantages of exosomes in vaccine preparation. Based on all of these, exosomes are emerging as a promising avenue for vaccine strategies.